Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/su14063141
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Microstructure Characteristics of Metakaolin-Based Geopolymer Mortars with High Water-to-Binder Ratios

Abstract: Geopolymers and other alkali-activated materials were investigated in detail as alternatives to ordinary Portland cement because of their reduced CO2 emissions, high (radionuclide) binding capacities, and low permeabilities. The last two properties make them potential materials for the immobilization of several types of chemical waste. In this context, the direct immobilization of liquid waste streams would be a useful application. This study aimed to develop geopolymers with high water-to-binder ratios, but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The shrinkage testing and theoretical research are more complex than investigating the mechanical properties of metakaolin-based geopolymers. Numerous studies have found that the mixture ratio (alkali activator content [17,18], slag content [18], fly ash content [19], and water-binder ratio [20]), curing method [17,21], and additives) significantly influences the volume stability of metakaolin-based geopolymers [22]. Fu et al [23] reported that metakaolin can coarsen the pore structure of hardened slag, thereby reducing autogenous and drying shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…The shrinkage testing and theoretical research are more complex than investigating the mechanical properties of metakaolin-based geopolymers. Numerous studies have found that the mixture ratio (alkali activator content [17,18], slag content [18], fly ash content [19], and water-binder ratio [20]), curing method [17,21], and additives) significantly influences the volume stability of metakaolin-based geopolymers [22]. Fu et al [23] reported that metakaolin can coarsen the pore structure of hardened slag, thereby reducing autogenous and drying shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…Its main raw material can be aluminosilicate minerals occurring in nature, or it can be made from solid industrial waste with a high aluminum-silicon content [2][3][4]. Studies have shown that blast furnace slag [5], zeolite [6], metakaolin [7], fly ash [8], red mud [9], and other synthetic geopolymers have many advantages, such as high strength, low toxicity substance leaching rates, good durability, etc. Such synthetic geopolymers are widely used in industrial applications such as brick-making and road construction.…”
Section: Introductionmentioning
confidence: 99%